Random bit multilevel algorithms for stochastic differential equations - Giles, MB; Hefter, M; Mayer, L; Ritter, K (Elsevier, 2019)
We study the approximation of expectations E(f(X)) for solutions X of SDEs and functionals f : C([0, 1], Rr) → R by means of restricted Monte Carlo algorithms that may only use random bits instead of random numbers. We consider the worst case setting for functionals f from the Lipschitz class w.r.t. the supremum norm. We construct a random bit multilevel Euler algorithm and establish upper bounds for its error and cost. Furthermore, we derive matching lower bounds, up to a logarithmic factor, that are valid for all random bit Monte Carlo algorithms, and we show that, for the given quadrature problem, random bit Monte Carlo algorithms are at least almost as powerful as general randomized algorithms.